Kajian Ekstraksi Karagenan Berdasarkan Variasi Rasio Rumput Laut (Eucheuma cottonii) dengan Nira Siwalan (Borrasus flaberina L.) dan Lama Perendaman serta Aplikasinya pada Bubuk Jelly Drink Nanas (Ananas comosus) - Alfajri Ula Ashfarina; Noor Harini; Listiari Hendraningsih (Universitas Muhammadiyah Malang, 2020)
The extraction of carrageenan by Eucheumma cottonii using siwalan neera as a solvent which contains pottasium 236mg per 100g and others mineral. Carragenan extract applied on pineapple jelly drink powder as a gelling agent by different concentration. This research was conducted into two stages by 3 times repitition. First, carrageenan extraction using a Factorial Randomized Block Design (RBD) consisting of 2 factors. The first factor is the ratio of seaweed with neera siwalan (S) (1:10, 1:20, 1:30) and second factor is extraction time (T) (60 minutes, 90 minutes, and 120 minutes). Extract of carrageenan was analyzed on yield, viscosity, gel strength, moisture content and ash content. The second stage is application of carrageenan extract on pineapple jelly drink powder (K) with carrageenan concentration differently (K) of 0.5%, 1%, 1.5%, 2%, 2.5%. The parameters analyzed in the second stage are viscosity, gel strength, syneresis, and organoleptic (taste, suction power, and mouthfeel). The results shows that there was a significant effect on the Siwalan neera ratio on the carrageenan produced on yield, viscosity, gel strength, water content. The best carrageenan at stage 1 was produced from the treatment of seaweed and neera siwalan ratio 1:30 with extraction time of 120 minutes (S3T3), namely yield 82.87%, moisture content 15.3%, ash content 15.97%, gel strength 102.95 g/cm2 and 5,3 cP viscosity. The addition of the best extract carrageenan to pineapple jelly drink and it was obtained the best result namely the addition of carrageenan 1% (K2) with viscosity of 2.3 cP, gel strength 8.6615 g/cm2, sineresis (24 hours) 0.9183%, sineresis (48 Hours) 3.5430%, and sineresis (72 Hours) 5.1905%, taste 3.3 (enough in tasting), suction power 3.75 (easy to suck) and mouthfeel 2.9 (enough to feel the gel).